A kárpátaljai németség szovjet hadifogolytáborokba hurcolása és internálása (1944–1946) - Molnár D. Erzsébet; Молнар Д. Єлизавета; Yelyzaveta Molnar D. („RIK-U” Kiadó, 2017)
Az 1941-es népszámlálási adatok szerint a német nemzetiségű lakosság száma Kárpátalján 13 222 fő volt.628 (1. ábra) Egyes források szerint ez a szám 1946-ra 10 600 főre csökkent.629 Más kútfők ettől lényegesen kevesebbre, mindössze 2338 főre teszik a régióban megmaradt németség számát.630 A német etnikum fogyatkozásának egyik oka volt, hogy 1944 őszére, a Vörös Hadsereg bejövetele előtt egy részük elhagyta Kárpátalja területét. A német lakosság számbeli csökkenésének másik oka az 1944 végén–1946 elején végbemenő, szovjetek által irányított, három szakaszból álló deportálási hullám volt.

Abstract. At the end of the World War II took place the most tragic events of the Transcarpathian Germans. According to the Doctrine of Collective Guilt the consequences of the lost World War for thousands of people belonging to these ethnics there were deportations and forced labor. The Soviet will to punish the German nations was also obvious in the case of Transcarpathia, as Stalin decided to attach this territory to the Soviet Union. Systematic, ruthless imposition of the Soviet regime began in Transcarpathia in October 1944, when the soldiers of the Soviet Army, exactly the 4th Ukrainian Front appeared in the region. The aim of the paper is to present the main aspects of the deportations and forced relocations of German civilian population from Transcarpathia in 1944-1946.
Dragging away to soviet pow camps and internment of Transcarpathian germans (1944–1946)
https://kmf.uz.ua/hu/kiadvanyaink/hadifogsag-malenkij-robot-gulag-karpat-medencei-magyarok-es-nemetek-elhurcolasa-szovjetunio-hadifogolyes-kenyszermunkataboraiba-1944-1953/
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00004138
Keywords: Kárpátalja; németek; hadifogolytábor; internálás; elhurcolás